Classroom observation tasks : a resource book for language teachers and trainers - Wajnryb, Ruth.; Cambridge University Press (Cambridge [England] ; New York : Cambridge University Press, 1992)
Classroom Observation Tasks shows how to use observation to learn about language teaching. It does this by providing a range of tasks which guide the user through the process of observing, analysing and reflecting, and which develop the skills of observation. The book contains a bank of 35 structured tasks which are grouped into seven areas of focus: the learner, the language, the learning process, the lesson, teaching skills and strategies, classroom management, and materials and resources. Each task looks at one aspect of a particular area; for example, the language a teacher uses to ask questions, or how the teacher monitors learning, or how people interact in a lesson. Each task provides guidance in how to record observations, and questions to help users interpret the data and relate the experience to their own teaching circumstances and practice. [This book]: a- is addressed mainly to teachers, but also caters for trainee teachers, teacher trainers and others involved in school-based teacher support, teacher development and trainer training; b- has a comprehensive introduction to the tasks and a rationale covering the theoretical issues involved; and c- places the responsibility for professional growth in the hands of the teacher.
-- Introduction -- The tasks: the learner -- Language -- Learning -- The lesson -- Teaching skills and strategies -- Classroom management -- Materials and resources.
Includes bibliographical references (pages 136-138) and index.
Keywords: Language teachers -- Training of; Observation (Educational method)